2021
DOI: 10.1029/2021gl096520
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Oxalate‐To‐Sulfate Ratio as an Aqueous Processing Marker: Similarity Across Field Campaigns and Limitations

Abstract: Leveraging aerosol data from multiple airborne and surface‐based field campaigns encompassing diverse environmental conditions, we calculate statistics of the oxalate‐sulfate mass ratio (median: 0.0217; 95% confidence interval: 0.0154–0.0296; R = 0.76; N = 2,948). Ground‐based measurements of the oxalate‐sulfate ratio fall within our 95% confidence interval, suggesting the range is robust within the mixed layer for the submicrometer particle size range. We demonstrate that dust and biomass burning emissions ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 108 publications
(164 reference statements)
0
2
1
Order By: Relevance
“…Recent work has attributed such high ratios to biomass burning influence. 115 Oxalate's concentration in this single sample was 130.76 ng m −3 in contrast to the summer median value of 92.77 ng m −3 , indicating that it was higher than normal.…”
Section: Resultscontrasting
confidence: 57%
“…Recent work has attributed such high ratios to biomass burning influence. 115 Oxalate's concentration in this single sample was 130.76 ng m −3 in contrast to the summer median value of 92.77 ng m −3 , indicating that it was higher than normal.…”
Section: Resultscontrasting
confidence: 57%
“…The presence of oxalate is linked to cloud processing due to its aqueous formation mechanism (Ervens et al., 2004 ; Li et al., 2020 ; Sorooshian et al., 2013 , 2015 ). Mass ratios of oxalate:sulfate in cloud droplet residual particles have been observed between 0.01 and 0.23, with larger ratios associated with aqueous phase processing occurring at higher cloud altitudes (Hilario et al., 2021 ; Wonaschuetz et al., 2012 ). Air masses for samples C2, C3, and C5 spent time aloft (Table S2 in Supporting Information S1 ), allowing more time for particles to chemically process in the aqueous‐phase, resulting in larger oxalate:sulfate ratios (0.08–0.18; Tables 1 and S3 in Supporting Information S1 ), compared to samples C1 and C4 (0.04 and 0.06, respectively) which spent more time within the MLD.…”
Section: Resultsmentioning
confidence: 99%
“…Another observation at the summit of Tai Mo Shan, Hong Kong, showed that the fraction of water‐soluble organic matter (WSOM) in aerosols increased during a post‐cloud period (T. Li et al., 2020). Oxalate is regarded as a tracer of in‐cloud aqueous‐phase reactions (Crahan et al., 2004; Hilario et al., 2021; Sorooshian et al., 2006, 2010) and is strongly correlated with sulfates, which are considered mainly generated by in‐cloud processes (Huang et al., 2006; Yu et al., 2005). Thus, the ubiquitous organic aerosol layers with elevated oxalic acid levels above the clouds indicate aqSOA formation after droplets evaporate (Sorooshian, Lu, et al., 2007).…”
Section: Introductionmentioning
confidence: 99%